Framing the concept of invasive species "impact" within a management context. (4th June 2020) - Barney, Jacob N.; Tekiela, Daniel R.
Abstract: Governments and conservation organizations worldwide are motivated to manage invasive species due to quantified and perceived negative ecological and economic impacts invasive species impose. Thus, determining which species cause significant negative impacts, as well as clear articulation of those impacts, is critical to meet conservation priorities. This process of determining which species warrant management can be straightforward when there are clear negative impacts, such as dramatic reductions in native diversity. However, the majority of changes to ecosystem pools and fluxes cannot be readily categorized as ecologically negative or positive (e.g., lower soil pH). Additionally, diverse stakeholders may not all agree on impacts as negative. This complexity challenges our ability to simply and uniformly determine which species cause negative impact, and thus which species merit management, especially as we expand invader impacts to encompass a more holistic ecosystem perspective beyond biodiversity and consider stakeholder perspectives and priorities. Thus, we suggest impact be evaluated in a context that is dictated by governing policies or conservation/land management missions with the support of scientists. In other words, within each jurisdiction, populations are identified as causing negative impact based on the hierarchical governing policies and mission of that parcel. Framing negative impact in a management context has the advantages of (1) easily scaling from individual landscapes to geopolitical states; (2) better representing how managers practice, (3) reflecting invasive species as spatially contextual, not universal, and (4) allowing for flexibility with dynamic ecosystems undergoing global change. We hope that framing negative impact in an applied context aids management prioritization and achieving conservation goals.